Stochastic Optimization in Disaster Relief Management - Fatmah Syarah, Herman Mawengkang, Anton Abdulbasah Kamil, Sutarman (International Journal of Advanced Science and Technology, 2020)
This research develops a two-stage stochastic programming model for planning the distribution of aid to areas affected by disasters during the emergency response. Taking into account 3 network locations of aid goods, namely (main warehouse or supplier, distribution center and disaster area) in the storage of relief goods inventory with standard assistance time or maximum delivery duration and penalty for loss of relief goods. To determine the number and location of suppliers and distribution centers propose a mixed integer programming model. Where demand for relief goods and routes are considered as variables containing uncertainty.